PENILAIAN KEAKTIFAN MAHASISWA DENGAN MENGGUNAKAN MODEL PENILAIAN PORTOFOLIO PADA PERKULIAHAN MORFOLOGI TUMBUHAN DI JURUSAN BIOLOGI UNIMED - Ashar Hasairin (LPPM Universitas Negeri Medan, 2012)
The objektive of research is to get the avchivement value of autodidactstudent in Plant Morfology lecture by using portofolio model evaluation. Theresearch method of examing avct is teaching by speech, discussion and questionanswer provided by slide teaching media chart in class, laboratory and in the field. The activity consists of cycle 1: Organum nutritivum); cycle 2: Organumreproduvctivum. Each cycle evaluation is provided by test (pretest – postest andpersonal task) in portofolio evaluation. The assesment of practice report based on thecompletion of observation data. Mean while the active assesment based on thedeligen, accuratiose corettness corettness and independence. The result of thisactifity is goined that petest and postest score in cycle 1 and 2 toward the score A,B, C and the degreasing of student quantity whivch gets score D and E in each item. Mean while category the scoring of personal task of cycle 1 and 2 wholly is verygood and good category (score A and B) category is higher than enough and lesscategory (Score C and D), not good category (score E) is not found. The teachingmodel by practice is more precice to do student can see directly their plant object. Meanwhile for the scoring task and paper writing student face probem in masteringliterature and terminology. The active student scoring of civcle 1 & 2 seemed thatthe adventage in correctness of understanding item and determining observedobject.